2004
DOI: 10.1007/s00234-004-1231-1
|View full text |Cite
|
Sign up to set email alerts
|

MR spectroscopy of cervical spinal cord in patients with multiple sclerosis

Abstract: MR spectroscopy (MRS) of the brain in patients with multiple sclerosis has been well studied. However, in vivo MRS of the spinal cord in patients with MR spectroscopy has not been reported to our knowledge. We performed MRS of normal-appearing cervical spinal cords in multiple sclerosis patients and in healthy controls. N-acetyl aspartate was shown to be reduced within the cervical spinal cord of multiple sclerosis patients when compared with healthy controls. This finding supports axonal loss and damage withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(26 citation statements)
references
References 11 publications
1
25
0
Order By: Relevance
“…A recent post-mortem study showed convincingly that a substantial damage to neurons occurs in the spinal cord of MS cases, with spinal interneurons being affected at all cord levels 21. Furthermore, quantitative MRI studies of the cervical cord in MS patients reported a reduction in N-acetylaspartate24 and cord GM magnetisation transfer alterations in both relapsing25 and progressive26 MS cases. With RRMS patients, the cord GM MT ratio has also been shown to contribute to their disability 25.…”
Section: Discussionmentioning
confidence: 98%
“…A recent post-mortem study showed convincingly that a substantial damage to neurons occurs in the spinal cord of MS cases, with spinal interneurons being affected at all cord levels 21. Furthermore, quantitative MRI studies of the cervical cord in MS patients reported a reduction in N-acetylaspartate24 and cord GM magnetisation transfer alterations in both relapsing25 and progressive26 MS cases. With RRMS patients, the cord GM MT ratio has also been shown to contribute to their disability 25.…”
Section: Discussionmentioning
confidence: 98%
“…In general, voxels with a volume of about 2 ml and located between C1–C3 (Ciccarelli et al, 2007, 2010) and C2–C3 (Marliani et al, 2007, 2010) have been used, although voxels positioned between C3 and C7 (Kendi et al, 2004) and between C6 and C7 (Henning et al, 2008), have been used. MRS in the lower cervical and thoracic cord is technically very difficult because receiver coils are generally less sensitive to these regions, the spinal cord is smaller, and the amount of vertebral bone is increased, causing further field inhomogeneities that make shimming challenging.…”
Section: Current State-of-the-art and How Challenges Are Being Addrementioning
confidence: 99%
“…Significant differences in NA, Cr, Cho and mI concentrations were observed between spinal cord and brainstem. A study in MS patients found reduced level of NAA in the cervical spinal cord in MS supporting the presence of axonal loss and damage in normal-appearing spinal cords of MS patients 82. Significant correlations were also observed between Cr, Cho, and mI levels in the cervical cord and disability, as measured by EDSS and 9-hole peg test 38…”
Section: Spectroscopymentioning
confidence: 93%